Bacterial and fungal viability in the preterm gut: NEC and sepsis. Issue 4 (20th February 2013) - Stewart, Christopher James; Nelson, Andrew; Scribbins, David; Marrs, Emma Clare L; Lanyon, Clare; Perry, John David; Embleton, Nicholas D; Cummings, Stephen Peter; Berrington, Janet Elizabeth
Abstract : Background and aims: Evidence suggests that microbial communities in the preterm gut may influence the development of necrotising enterocolitis (NEC) and sepsis. Existing data often neglect fungi and whether bacteria were metabolically active or not. We sought to characterise the bacterial and fungal stool flora of preterm neonates and organism viability and evaluate any associations with NEC and sepsis. Patients: 136 stools from 32 patients (<32 weeks gestation) were collected between birth and day 95. Seven infants developed NEC and 13 sepsis. Methods: Stools were analysed by PCR-DGGE for assessment of the total bacterial and fungal communities by analysis of 16S rRNA and 28S rRNA, respectively. In 65 samples (25 infants), the viable (RNA) bacterial and fungal communities were analysed. Analyses were performed to examine the possible effects of demographic or treatment related factors and the development of NEC or sepsis. Results: 80 (66 viable) bacterial species were identified overall and 12 fungal (none viable). Total bacterial communities significantly differed between healthy infants and those with NEC or sepsis, with Sphingomonas spp. significantly associated with NEC. Significant drivers of community structure differed based on either total or viable analysis. Antifungal prophylaxis was associated with altered bacterial community and a reduction in bacterial richness was observed in week 4, correlating with high antibiotic exposure. Conclusions: Total and viable communities differ in preterm infants, and non-viable fungal species are present in infants on fungal prophylaxis. Exploration of viability and non-bacterial contributors to the total community may increase understanding of NEC and sepsis.